1924 Ga. Laws 283 - (:unkn) unknown (My University, 1924)
An Act for the Protection of Game Birds in the County of Bartow, § 2: Prohibited hunting any game bird or animal within the county limits of Bartow using an automatic or repeating shotgun. Violators guilty of a misdemeanor.
Keywords: HUNTING REGULATION